Building Adolescents’ Confidence in Understanding Puberty through Interactive Educational Media - Harahap, Jumli Sabrial; Masril, Masril; Darimis, Darimis; Susandra, Elsadina (Help: Journal of Community Service, 2025)
Adolescents often experience uncertainty and discomfort when discussing puberty due to limited knowledge, social stigma, and the lack of safe learning environments. Interactive visual media offers potential to simplify complex biological concepts while encouraging open communication. This community service program aimed to enhance adolescents’ understanding of puberty and their confidence in discussing related topics through an engaging, interactive educational intervention. The program employed a participatory pretest–posttest design involving 14 adolescents aged 12–15 years. Activities included visual flash cards, scenario discussions, group-based learning tasks, and reflection sessions. A structured questionnaire measured knowledge and confidence before and after the intervention. Quantitative data (pretest–posttest scores and N-gain) were analyzed descriptively, while qualitative observations captured behavioral and communicative changes during sessions. Findings showed a substantial improvement in puberty knowledge, with mean scores increasing from 66.71 to 108.42 and an N-gain of 0.50. Observational data also indicated enhanced confidence, greater willingness to speak, improved peer interaction, and reduced hesitation when discussing sensitive issues. Participants reported feeling more supported and emotionally prepared to understand puberty-related changes. The integration of visual-interactive media supported cognitive processing in line with multimedia learning theories, while collaborative activities aligned with social constructivist principles. The safe learning environment created by facilitators also helped reduce emotional barriers, consistent with adolescent psychosocial development literature. These factors collectively strengthened both cognitive and psychosocial outcomes. Interactive visual media effectively improved adolescents’ understanding and confidence regarding puberty.